NTRK fusion protein expression is absent in a large cohort of diffuse large B-cell lymphoma - Ghandili, Susanne; Dierlamm, Judith; Bokemeyer, Carsten; von Bargen, Clara Marie; Weidemann, Sören Alexander (Frontiers in Oncology, 2023)
Even though two NTRK-targeting drugs are available for the treatment of irresectable, metastatic, or progressive NTRK-positive solid tumors, less is known about the role of NTRK fusions in lymphoma. For this reason, we aimed to investigate if NTRK fusion proteins are expressed in diffuse large B-cell lymphoma (DLBCL) by systemic immunohistochemistry (IHC) screening and additional FISH analysis in a large cohort of DLBCL samples according to the ESMO Translational Research and Precision Medicine Working Group recommendations for the detection of NTRK fusions in daily practice and clinical research. A tissue microarray of 92 patients with the diagnosis of DLBCL at the University Hospital Hamburg between 2020 and 2022 was built. The clinical data were taken from patient records. Immunohistochemistry for Pan-NTRK fusion protein was performed and positive staining was defined as any viable staining. For FISH analysis only results with quality 2 and 3 were evaluated.NTRK immunostaining was absent in all analyzable cases. No break apart was detectable by FISH. Our negative result is consistent with the very sparse data existing on NTRK gene fusions in hematologic neoplasms. To date, only a few cases of hematological malignancies have been described in which NTRK-targeting drugs may provide a potential therapeutic agent. Even though NTRK fusion protein expression was not detectable in our sample cohort, performing systemic screenings for NTRK fusions are necessary to define further the role of NTRK fusions not only in DLBCL but in a multitude of lymphoma entities as long as the lack of reliable data exists.